Vacuum-Assisted Continuous Circular Capsulorhexis Using Bimanual Irrigation and Aspiration System of Phaco Machine in Immature Cataract - ÖKSÜZ, HÜSEYİN; Daglioglu, Mutlu C.; Coskun, Mesut; Ilhan, Ozgur; Tuzcu, Esra Ayhan; Ilhan, Nilufer; Ayintap, Emre; Keskin, Ugurcan; Taskin, Ibrahim (My University, 2013)
Seventy-eight eye of 65 patients were enrolled in this retrospective clinical study. Two-side ports are made with a 23-gauge stiletto knife. The irrigation handpiece is introduced into the anterior chamber through one side port and 27-gauge cystotome is introduced through the other one. Anterior capsular flap is created with cystotome. The capsular flap is vacuumed with a 25-gauge visco elastic-s cannula, which connected to the phaco machine vacuum. The continuous circular capsulorhexis (CCC) is completed with the using bimanual irrigation and aspiration system of phaco machine. Vacuum-assisted CCC technique was used in 78 cases of uncomplicated immature senile cataracts. All cases were done under sub-Tenon-s anesthesia. A complete CCC was achieved in all cases. Performing CCC with our technique is easy, safe, and cheap. It may be an alternative method to CCC by using OVD and forceps.
Keywords: Immature Cataract